2014
DOI: 10.4056/sigs.5059132
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of invertebrate iridovirus IIV22A, a variant of IIV22, isolated originally from a blackfly larva

Abstract: Members of the family Iridoviridae are animal viruses that infect only invertebrates and poikilothermic vertebrates. The invertebrate iridoviruses 22 (IIV22) and 25 (IIV25) were originally isolated from a single sample of blackfly larva (Simulium spp., order Diptera) collected from the Ystwyth river near Aberystwyth, Wales. Recently, the genomes of IIV22 (197.7 kbp) and IIV25 (204.8 kbp) were sequenced and reported. Here, we describe the complete genome sequence of IIV22A, a variant that was isolated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The MCP of Liz–CrIV is not only 8 aa longer than that of IIV6, but it has 13 additional mutation sites (Figure S1). This rate of MCP divergence (5.5%/4.5% for nt/aa) is smaller than that found between two separate types/species: E.g., IIV1 (Tipula iridescent virus; TIV) and IIV22 (Simulium iridescent virus; SIV; 19.8%/9.7%) [51], but much greater than those between two variants of the same type e.g., IIV22 and IIV22A (1.3%/0%) [52] or IIV31 and PjIV. Similarity plot analysis supported the hypothesis of recombination downstream of the MCP gene and the closest relationship of this region to the homologous regions of polyiridoviruses, e.g., IIV9 ORF011 , adjacent to the IIV9 MCP gene ( ORF010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MCP of Liz–CrIV is not only 8 aa longer than that of IIV6, but it has 13 additional mutation sites (Figure S1). This rate of MCP divergence (5.5%/4.5% for nt/aa) is smaller than that found between two separate types/species: E.g., IIV1 (Tipula iridescent virus; TIV) and IIV22 (Simulium iridescent virus; SIV; 19.8%/9.7%) [51], but much greater than those between two variants of the same type e.g., IIV22 and IIV22A (1.3%/0%) [52] or IIV31 and PjIV. Similarity plot analysis supported the hypothesis of recombination downstream of the MCP gene and the closest relationship of this region to the homologous regions of polyiridoviruses, e.g., IIV9 ORF011 , adjacent to the IIV9 MCP gene ( ORF010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the phylogenetic analyses of proteins encoded by IIV3, IIV6 (Jakob et al , 2001) and IIV9 (Wong et al , 2011) have revealed that IIV9 is more closely related to IIV3 than to IIV6. This has been confirmed with IIV22, IIV22A, IIV25 and IIV30, four close relatives of IIV9 (Piégu et al , 2013a, b, c, d), indicating that some species of the genus Iridovirus are more closely related to members of the genus Chloriridovirus than to other Iridovirus species from insects. Consequently, this suggests that the genus Iridovirus contains several diverse species or species complexes.…”
Section: Full Textmentioning
confidence: 63%
“…To date, six genomes of IIVs have been sequenced: IIV3, the mosquito iridescent virus (Delhon et al , 2006), IIV6, the Chilo iridescent virus (Jakob et al , 2001), IIV9, the Wiseana iridovirus (Wong et al , 2011), IIV22 (Piégu et al , 2013a), IIV22A (Piégu et al , 2013b), IIV25 (Piégu et al , 2013c) and IIV30 (Piégu et al , 2013d). Here, we present a summary classification and a set of features for IIV31, the eighth IIV sequenced, together with the description of the sequencing and annotation of its genome.…”
Section: Full Textmentioning
confidence: 99%
“…Moreover, invertebrate iridoviruses (family Iridoviridae ), have been identified in blackfly larvae across the globe (Piégu et al . 2013, 2014a, 2014b). In addition, the most studied arbovirus transmitted by blackflies is vesicular stomatitis virus (family Rhabdoviridae; genus Vesiculovirus ), that typically infects cattle, horses, and swine (Howerth, Mead and Stallknecht 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Kraberger et al described the ssDNA virome of blackflies in New Zealand and reported high numbers of Genomoviridae, Circoviridae and Microviridae (Kraberger et al 2019). Moreover, invertebrate iridoviruses (family Iridoviridae), have been identified in blackfly larvae across the globe (Piégu et al 2013(Piégu et al , 2014a(Piégu et al , 2014b. In addition, the most studied arbovirus transmitted by blackflies is vesicular stomatitis virus (family Rhabdoviridae; genus Vesiculovirus), that typically infects cattle, horses, and swine (Howerth, Mead and Stallknecht 2002).…”
Section: Introductionmentioning
confidence: 99%